PENGARUH PELATIHAN TERHADAP KINERJA APARATUR SIPIL NEGARA (ASN) PADA DINAS PERTANIAN KABUPATEN BANTAENG - Mega Utami (CV. Adiba Aisha Amira, 2024)
This research aims to find out the influence of training on the performance of State Civil Apparatus (ASN) at the Bantaeng Regency Agriculture Service. The number of samples used was 70 employees of the Bantaneng Regency Agriculture Service using saturated samples. Data collection was carried out using the questionnaire method. The data analysis technique used is simple linear regression analysis using Statistical Product and Service Solution (SPSS). The results of this research show that the quality of training (X) has a positive and significant influence on employee performance (Y). The training variable has a very strong relationship with the employee performance variable with an influence percentage of 54.6%.